Clinical Sports Medicine - Chan YS; Ho CS (Deutsche Zeitschrift für Sportmedizin, 2021)
Background: This study investigates the efficacy of an adapted physical activity program on reaction performance in children with attention deficit hyperactivity disorder (ADHD).Methods: Study participants consist of 37 children with ADHD aged 8 -11 years old, were divided into intervention and control groups. The intervention consisted of a 60-minute adapted physical exercise program occurring two times per week for eight weeks. This intervention program, which combined both aerobic and perceptual-motor exercise characteristics, was designed with a diverse set of exercise games. Two tests of joystick were employed: a simple reaction time test (SRT), and a four-choice reaction time test (CRT).Results: Our results showed that whole group (pretest: 808243 ms; posttest: 714197 ms, p<0.05), boys (pretest: 764277 ms; posttest: 685228 ms, p<0.05), and girls (pretest: 91856 ms; posttest: 78851 ms, p<0.05) had reduced CRT in the intervention group but not in the control group, and there was no significant change in the variability of SRT and CRT in all groups.Conclusion: Our study found that the adapted physical exercise used in this study influenced the performance of a sensory-dependent cognitive task of children with ADHD. This confirms that exercise can be a useful intervention tool for these children, especially those who are looking to improve these aspects of their executive functions and complicated sensorimotor ability.Key Words: Exercise Games, Information Processing, Executive Function, Reaction Time